1998
DOI: 10.1111/j.1600-0846.1998.tb00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance coil for 31P spectroscopy of skin over curved body surfaces

Abstract: Increasing the area of skin sampled while maintaining selectivity to limit muscle contamination, relying simply on coil geometry, is practical using a parallel configuration of long narrow strip coils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…In a preliminary study on human abdominal skin biopsies we justified the use of the terms freezable/unfreezable water instead of free/bound water rather reserved to vibrational or relaxational techniques. The present DSC study shows that the freezable water (that covers bulk water in excess but also confined water in mesopores) roughly represents two‐third of the total water in human skin in accordance with previous NMR, DVS, and DSC results . One‐third of the total water of human skin is unfreezable water, corresponding to the filling of the first hydration shell of proteins and other hydrophilic components.…”
Section: Resultssupporting
confidence: 91%
“…In a preliminary study on human abdominal skin biopsies we justified the use of the terms freezable/unfreezable water instead of free/bound water rather reserved to vibrational or relaxational techniques. The present DSC study shows that the freezable water (that covers bulk water in excess but also confined water in mesopores) roughly represents two‐third of the total water in human skin in accordance with previous NMR, DVS, and DSC results . One‐third of the total water of human skin is unfreezable water, corresponding to the filling of the first hydration shell of proteins and other hydrophilic components.…”
Section: Resultssupporting
confidence: 91%
“…Using both a depth-selective surface coil 12 mm in diameter and a phase-encoding method generating 0.5 mm thick slices parallel to the skin surface, the present authors' group was unable to detect significant phosphorus signals out of the noise, with acquisition times of the order of 1 h even with a dedicated HTS 31 P surface coil with a loaded quality factor of several thousand. However, the detection of phosphorus compounds by spectroscopy of isolated perfused viable epidermal sheets from pigs (29) suggests that, by increasing the acquisition time and/or the sensitive surface of an HTS surface coil, it should be possible to measure precisely localized phosphorus spectra of in vivo skin and thus explore skin physiology in normal and pathological conditions.…”
Section: Chemical Parametersmentioning
confidence: 99%
“…Hyde et al reported a magnetic field profile that penetrated approximately half of the spacing of the two coils (Hyde et al, 1987). Similarly, Bohning et al used surface coil meander-line and parallel array technology to study 31 P on surface tissues using magnetic resonance spectroscopy (MRS)(Bohning et al, 1998). Illustrated in Figure 6 is the geometry, simulated and optimized in Ansoft HFSS, for a SRA structure at X-band.…”
Section: Resultsmentioning
confidence: 99%